2019
DOI: 10.1111/jcmm.14827
|View full text |Cite
|
Sign up to set email alerts
|

LIN28A gene polymorphisms modify neuroblastoma susceptibility: A four‐centre case‐control study

Abstract: Neuroblastoma ranks the most common seen solid tumour in childhood. Overexpression of LIN28A gene has been linked to the development of multiple human malignancies, but the relationship between LIN28A single nucleotide polymorphisms (SNPs) and neuroblastoma susceptibility is still under debate. Herein, we evaluated the correlation of four potentially functional LIN28A SNPs (rs3811464 G>A, rs3811463 T>C, rs34787247 G>A, and rs11247957 G>A) and neuroblastoma susceptibility in 505 neuroblastoma patients and 1070 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Our study demonstrated that LIN28A polymorphisms were not significantly associated with HB susceptibility. However, LIN28A rs34787247 G>A has been reported to be connected to increased risk of neuroblastoma and LIN28A rs3811463 T>C and rs34787247 G>A to increased risk of nephroblastoma 27 , 28 . Moreover, a study in East Asia showed that SNPs of LIN28A (rs11247954, rs12728900, rs3811463, rs4274112, rs4659441, rs6598964, and rs6683792) were not significantly associated with breast cancer risk 43 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study demonstrated that LIN28A polymorphisms were not significantly associated with HB susceptibility. However, LIN28A rs34787247 G>A has been reported to be connected to increased risk of neuroblastoma and LIN28A rs3811463 T>C and rs34787247 G>A to increased risk of nephroblastoma 27 , 28 . Moreover, a study in East Asia showed that SNPs of LIN28A (rs11247954, rs12728900, rs3811463, rs4274112, rs4659441, rs6598964, and rs6683792) were not significantly associated with breast cancer risk 43 .…”
Section: Discussionmentioning
confidence: 99%
“…showed that the downregulation of LIN28A expression suppressed differentiation and self-renewal of human breast cancer stem cells by inactivating the Wnt pathway in a let-7b-dependent manner 41 . A case-control study at four centers demonstrated that LIN28A gene polymorphisms alter susceptibility to neuroblastoma; it was found that LIN28A SNPs, particularly rs34787247 G>A, could increase neuroblastoma risk 28 . Also, LIN28A rs3811463 T>C and rs34787247 G>A have been associated with increased risk of Wilms tumor in Chinese children 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimation of haplotype frequency and the analysis of their effect on neuroblastoma risk were performed using logistic regression analysis. 46 , 52 We also applied the FPRP analysis to evaluate noteworthy associations by the means as described elsewhere. 53 , 54 In brief, three parameters were employed to determine FPRP values, statistical power, p value, and prior probability π representing a real association between the SNP and a disease.…”
Section: Methodsmentioning
confidence: 99%
“…Logistic regression analyses were adopted to obtain haplotype frequencies and distinct haplotypes, with the adjustment for gender and age. 51 , 52 FPRP analysis was further conducted to examine whether significant results are just chance findings or noteworthy, as described elsewhere. 53 , 54 We also performed the eQTL analysis using the GTEx portal web site ( https://www.gtexportal.org/home/ ) to predict potential associations between the SNPs and gene-expression levels.…”
Section: Methodsmentioning
confidence: 99%